Examining the Relation Between Estimated Life Expectancy and Delinquency Across Development: an Examination of Adolescent Males Following Their First Arrest - Knowles, Alissa (Journal of developmental and life-course criminology, 2022)
Adolescents who anticipate a shorter lifespan are more likely to engage in reckless behavior, but few studies consider whether an adolescent’s estimated life expectancy (ELE) demonstrates change across development. This study examined whether ELE changes over time, and if these changes are associated with within-person changes in delinquency in 1147 males who had been arrested for the first time. An accelerated cohort design provided data for youth aged 14–21. Estimated life expectancy showed linear change, suggesting that adolescents grow more optimistic about their life expectancy as they age. Within person, increases in ELE were associated with decreased offending, a pattern consistent across development. These findings support the utility of ELE as a target for intervention in reducing adolescent crime.